Kontribusi Cyber Wellness terhadap Online Disinhibition pada Mahasiswa yang Aktif Menggunakan Media Sosial - Sujaya, Mutiara; Mardianto, Mardianto; Kurniawan, Rizal; Santoso, Indriyani (ARZUSIN, 2024)
This study used quantitative methods with a correlational approach. The population in this study was students who actively used social media totaling 212 samples. Sampling using purposive sampling technique. This study used a Cyber Wellness scale of 14 items with a coefficient of 0.816 and an Online Disinhibition scale of 25 items with a coefficient of 0.874. Data analysis, using simple regression techniques yielded a correlation coefficient of 0.542 with a p value (significant) of 0.000< 0.05, so it can be concluded that H1 is accepted and H0 is rejected. The results of the hypothesis test contained an R Square value of 0.293, thus the contribution of Cyber Wellness to resilience was 8%. The results showed that there was a contribution of Cyber Wellness to Online Disinhibition in college students who actively used social media with a negative relationship direction.